The Process of Thermodialysis and Some of its Possible Consequences in Biology - F.S. Gaeta; D.G. Mita (CHIMIA)
The flow of thermal energy in liquids is associated with the development of ponderomotive forces. In non-isothermal ionic or molecular solutions a drift of the disperse phase is thus produced (thermal diffusion). It is discussed here how thermal diffusion may have enriched or, respectively, depleted the primeval soup in some of the various materials originally present in the oceans. In particular life would, accordingly, have been reared in a potassium-enriched, sodiumdepleted cradle. The flow of heat across permeable partitions also causes processes of active transport of matter, which turn out to be closely related to thermal diffusion. These phenomena have been labelled by us with the name of “Thermodialysis”. It is further suggested here that the flux of metabolic heat through biological membranes produces active transport in living systems in a way analogous to the one which we have demonstrated to work in artificial porous septa. Localized sources of heat consisting in sites of enzymatic activity situated near to or in the cellular membrane itself, could in turn contribute intense pulsed fluxes of heat right at the site of the hypothetical membrane “pores”. Some probable characteristics of such biological“ pores” are also briefly discussed.